Coaching to prepare students for their school-to-work transition: conceptualizing core coaching competences. Issue 3 (7th February 2022) - van der Baan, Niels; Gast, Inken; Gijselaers, Wim; Beausaert, Simon
Abstract : Purpose: The present study proposes coaching as a pedagogical intervention to prepare students for transitioning to the labour market. Taking a competence-based approach, the proposed coaching practice aims to enhance students' employability competences to facilitate a smoother school-to-work transition. However, what transition coaching looks like remains largely unclear. Moreover, in competence-based education, teachers are expected to be highly skilled coaches, facilitating students' transition to the labour market. The present study aims to map the core competencies of a transition coach. Design/methodology/approach: A qualitative design was adopted to map the core competences of a transition coach. Data were collected from two focus groups, consisting of coaches in higher education and in the workplace. Findings: Results show that, to create the necessary support conditions, a coach creates a safe coaching environment and supports students in setting goals, guide them in the activities they undertake to attain these goals, and asks reflective questions. Moreover, the coach stimulates students' ownership by putting the student in the centre of the decision-making process. Furthermore, the results emphasize the importance of the coach's professional attitude and knowledge about the transition process and the labour market. Practical implications: The article concludes with practical implications for novice transition coaches and teachers in higher education. Originality/value: The present study adds to the agenda of graduate work readiness by proposing a coaching practice aimed at preparing students for their transition to the labour market.